PERSEPSI DOSEN TERHADAP PEMANFAATAN CHATGPT SEBAGAI ASISTEN AKADEMIK DALAM MENDUKUNG PEMBELAJARAN BERBASIS OUTCOME-BASED LEARNING (OBE) - Aeni Latifah; Dede Ridwan; Eki Agustin; Amelia Putri; Endang Supiani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The digital era has brought a significant transformation to higher education through the integration of artificial intelligence (AI) technologies as instructional support tools. ChatGPT is a generative AI application with the potential to support the implementation of Outcome-Based Learning (OBE), a learning model that emphasizes the achievement of competencies and measurable learning outcomes. This study aims to examine lecturers’ perceptions of the utilization of ChatGPT as an academic assistant in the context of OBE implementation in higher education institutions. The study is conducted through a literature review of empirical studies and contemporary analyses addressing the accelerated adoption of AI in education. The findings indicate that lecturers’ perceptions tend to be diverse; while many lecturers acknowledge the potential benefits of ChatGPT in enhancing the efficiency of instructional material development and providing formative learning support, concerns remain regarding academic integrity and pedagogical readiness for the effective use of this technology. Keywords: ChatGPT, Lecturers’ Perceptions, Outcome-Based Learning, Academic Assistant, Artificial Intelligence.